KEARIFAN LOKAL DALAM PEMANFAATAN TUMBUHAN UNTUK MENGATASI PENYAKIT DIABETES MELLITUS OLEH PENGOBAT TRADISIONAL DI KECAMATAN AMBALAU KABUPATEN BURU SELATAN - Pangemanan, Victory O; Ukratalo, Abdul M; Loilatu, Muhammad Fitrah; Ichsan, Muh. Nurhidayat; Pattimura, Nadira; Manery, Dodikrisno E (STIKES Pasapua Ambon, 2023)
Introduction: Diabetes is a condition in which metabolism is disrupted. The large number of people who live in rural areas, especially in areas that are difficult to reach (isolated), makes it difficult to implement even distribution of development results such as education and health. Method: This research is a form of descriptive qualitative research with an exploratory observational design. Results: There are 6 types of plants used as diabetes mellitus medicine, namely sugar apple, horse grass, suruhan, lantana, antawali and castor oil. The plant parts used as medicine for diabetes mellitus are leaves, herbs and stems. Conclusion: Annona squamosa, Panicum maximum, Peperomia pellucida, Lantana camara, Tinospora crispa and Jatropha curcas L plants have potential as diabetes mellitus drugs.